2021
DOI: 10.1101/2021.11.23.469747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide characterization of SARS-CoV-2 cytopathogenic proteins in the search of antiviral targets

Abstract: Therapeutic inhibition of critical viral functions is important for curtailing coronavirus disease-2019 (COVID-19). We sought to identify antiviral targets through genome-wide characterization of SARS-CoV-2 proteins that are crucial for viral pathogenesis and that cause harmful cytopathic effects. All twenty-nine viral proteins were tested in a fission yeast cell-based system using inducible gene expression. Twelve proteins including eight non-structural proteins (NSP1, NSP3, NSP4, NSP5, NSP6, NSP13, NSP14 and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 61 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Based on the ORF3a protein structural analysis ( Kern et al, 2021 ), we found a unique diG motif between the anti-parallel β4 and β5 sheets. These two glycine residues are part of a type II β-turn that could potentially be critical in maintaining the protein structure ( Zhang et al, 2022a ). Since the dCR1 deletion covers the diG residues, and we previously showed that deletion of the G188 residue (dG188) significantly enhanced the cytopathic effect of ORF3a ( Zhang et al, 2022a ; Zhang et al, 2022b ), we decided to focus on characterizing the possible role of the diG residues in intracellular transport.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the ORF3a protein structural analysis ( Kern et al, 2021 ), we found a unique diG motif between the anti-parallel β4 and β5 sheets. These two glycine residues are part of a type II β-turn that could potentially be critical in maintaining the protein structure ( Zhang et al, 2022a ). Since the dCR1 deletion covers the diG residues, and we previously showed that deletion of the G188 residue (dG188) significantly enhanced the cytopathic effect of ORF3a ( Zhang et al, 2022a ; Zhang et al, 2022b ), we decided to focus on characterizing the possible role of the diG residues in intracellular transport.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the current literature, the ORF3a (Open-Reading Frame 3a) protein of SARS-CoV-2 could be one of the viral proteins that contribute to COVID-19, as it is well-known for its role in viral pathogenesis and its activities have been linked to cell death and tissue damages ( Ren et al, 2020 ; Silvas et al, 2021 ; Zhang et al, 2022a ; McGrath et al, 2022 ), induction of cytokine storm that is a major cause of COVID-19-related death ( Siu et al, 2019 ; Xu et al, 2022 ) and the severity of COVID-19 ( Issa et al, 2020 ; Majumdar and Niyogi, 2020 ; Lednicky et al, 2021 ; Nagy et al, 2021 ). Furthermore, ORF3a is uniquely shared by SARS-CoV and SARS-CoV-2 within the genus of β-coronaviruses ( Kern et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its RNA encodes four major structural proteins, which include spike protein (S), envelope protein (E), membrane protein (M), and nucleocapsid protein (N) (41) [Figure 1]. Besides, 16 nonstructural proteins (NSPs) and 9 accessory proteins are included in the 29 proteins encoded (42).…”
Section: Structure Of Sars-cov-2mentioning
confidence: 99%